Note on the Occurrence of Cryptic and Endangered Mycoheterotrophic Orchid Galeola falconeri Hook.F. from Western Himalaya - Rai, Ishwari Datt; Jalal, Jeewan Singh; Singh, Gajendra; Rawat, Gopal Singh (Indian Forester, 2017)
No Abstract.